Should I use my imagination?' An attempt at co-designing a game editor within an app for alternative communication with children with autism - Pontual Falcão, Taciana; Machado, Karina; Pinto Neto, Zózimo; Miranda, Alinny; Cavalcanti, Ana Paula; Rodrigues, Paulo; Pereira, Carlos; Nascimento, André (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Within the spectrum of autism, there are children who are unable to communicate orally, which places severe barriers to their education and integration to society. Augmentative and Alternative Communication (AAC) technologies assist these children in expressing themselves, usually through a card-based interface. AAC apps became very popular in schools, helping educators to include children with disabilities in learning activities. In this context, new possibilities that go beyond communication emerge from the teachers and students' creativity, in particular the creation of playful educational content using these apps. However, as AAC apps were not designed for this goal, there are many limitations when users attempt to make these adaptations. This situation motivated the experience presented in this paper, where we worked with teachers and children with autism who already used the Livox AAC app, to design a new module with the aim of providing the necessary tools for creating games in the context of alternative communication, while still maintaining accessibility. The experience reinforced the importance to think about alternative methods of co-design and be ready to adapt when co-designing with children with autism, so that they can effectively contribute to the design process, having their opinions, wishes and capabilities truly taken into account.